Vascular Adhesion Protein-1 Determines the Cellular Properties of Endometrial Pericytes - Gharanei, Seley; Fishwick, Katherine; Peter Durairaj, Ruban; Jin, Tianrong; Siamantouras, Eleftherios; Liu, Kuo-Kang; Straube, Anne; Lucas, Emma S.; Weston, Christopher J.; Rantakari, Pia; Salmi, Marko; Jalkanen, Sirpa; et al. (Frontiers in Cell and Developmental Biology, 2021)
Vascular adhesion protein-1 (VAP-1) is an inflammation-inducible adhesion molecule and a primary amine oxidase involved in immune cell trafficking. Leukocyte extravasation into tissues is mediated by adhesion molecules expressed on endothelial cells and pericytes. Pericytes play a major role in the angiogenesis and vascularization of cycling endometrium. However, the functional properties of pericytes in the human endometrium are not known. Here we show that pericytes surrounding the spiral arterioles in midluteal human endometrium constitutively express VAP-1. We first characterize these pericytes and demonstrate that knockdown of VAP-1 perturbed their biophysical properties and compromised their contractile, migratory, adhesive and clonogenic capacities. Furthermore, we show that loss of VAP-1 disrupts pericyte-uterine natural killer cell interactions in vitro. Taken together, the data not only reveal that endometrial pericytes represent a cell population with distinct biophysical and functional properties but also suggest a pivotal role for VAP-1 in regulating the recruitment of innate immune cells in human endometrium. We posit that VAP-1 could serve as a potential biomarker for pregnancy pathologies caused by a compromised perivascular environment prior to conception.